Pengelolaan Arsip Elektronik di Unit Kearsipan PT Semen Padang - Putra, Wido Indra; Nelisa, Malta (Universitas Negeri Padang, 2020)
AbstractThe purpose of this paper is to describe how the stages of archival storage using the E-Archive application in the PT Semen Padang Archive Unit. describe how the stages of discovery of archives by using the E-Archive application in the PT Semen Padang Archive Unit. Based on the research that has been done, it can be concluded as follows. 1) Stages of archival storage using the E-Archive application at the Kerasipan Union PT Semen Padang, (a) preparing official letters or manuscripts that will be provided, (b) scanning scripts or letters, (c) creating folders on the computer as a repository for scanned letters or official scripts, (d) creating hyperlinks, namely linking the list of archives with the results of the scan, making complete administration of the media expert, consisting of, decree, minutes of approval of the transfer of media, minutes of legalization of transfer of media, list of archives suggested by media experts, and list of archives over media. 2) The stages of finding an archive using the E-Archive application in the PT Semen Padang Archive Unit are by (1) determining the types of letters needed, (2) searching for codes based on names or titles that have been indexed in the E-Archives application, after entering the title or code you want to find, the subject of the archive that you want to use appears.Keywords: E-Arhcive, storage.